Decreased cord blood estradiol levels in related to mothers with gestational diabetes. Issue 21 (May 2017) - Qi, Xiuyu; Gong, Bo; Yu, Jing; Shen, Limin; Jin, Wanling; Wu, Zhenmin; Wang, Jieyun; Wang, Jie; Li, Zhiqi
Abstract : Abstract: Recent studies have revealed a link between estradiol (E2 ) and glucose homeostasis. We aimed to assess the association between cord blood hormone levels and the risk of gestational diabetes mellitus (GDM). A total of 204 pregnant women with GDM and 204 pregnant women without GDM (control) were included in the study. Maternal GDM were diagnosed using a 75 g oral glucose tolerance test at 24 to 26 weeks of gestation. Cord blood samples from neonates were collected immediately post delivery. Controls, which were randomly selected from the study population, were matched (cases to controls ratio: 1:1) to cases by age, sex of fetus, and gestational week. Pregravid body mass index (BMI) (mean ± standard deviation) was (GDM vs. control): 24.5 ± 2.1 versus 22.8 ± 2.4 ( P  = .001). Cord blood estradiol in the GDM group was significantly lower than in the control group ( P  < .05). Pregravid BMI in the GDM group was significantly higher than in the control group ( P  < .05). Estradiol concentrations in cord blood were negatively correlated with birth weight ( r  = −0.121, P  < .05). Conditional logistic regressions showed pregravid BMI, cord blood estradiol, and parity independently and positively predicted GDM. Multivariable regression splines characterize a nonlinear relationship between cord blood estradiol and GDM risk. These results demonstrate a relationship between cord blood estradiol levels and GDM. Estradiol might be involved in the pathophysiology of GDM. Further studies are needed to explore potential mechanism.